Trichosanthes (Cucurbitaceae) in Malesia: additions and corrections, including a new species and a new variety - WJJO De Wilde (BRIN Publishing (Penerbit BRIN), 2012)
Recent discoveries in Trichosanthes (Cucurbitaceae): including the re-description of T. celebica, T. pedicellata spec. nov., and T. edulis var. punctata var. nov. are presented.